The Progression of Haze Formation in Rabbit Corneas Following Phototherapeutic Keratectomy - Gibson, Daniel J. (The Association for Research in Vision and Ophthalmology, 2013)
PURPOSE. To determine the topographical location and time course of development of corneal haze in a phototherapeutic keratectomy model using slit lamp examination, macrophotography, quantitative image analysis, and immunofluorescence staining of corneal sections. METHODS. Rabbit corneas were ablated with an excimer laser and were observed and graded for haze via slit lamp, imaged, and graded by macrophotography. Corneal sections were stained for α-smooth muscle actin (α-SMA) and tenascin-C (TNC). The distribution of haze imaged in the macrophotographs and density of α-SMA and TNC staining were compared. A daily image time course of haze formation was generated using macrophotography. RESULTS. The first signs of corneal haze were apparent shortly after reepithelialization. The haze was distributed as a ring at the wound margin in all cases, while nearly all corneas also had some central islands of haze initiation. With time, the haze spread within the ablated zone and intensified. The pattern of immunofluorescent staining for α-SMA and TNC at the wound margin mirrored the haze distribution, spread, and intensification with time. CONCLUSIONS. The initiation and spread of subepithelial haze begins shortly after reepithelialization. The haze then spreads from the loci of initiation and becomes more dense with time, maturing as early as 14 days after wounding. The improved temporal and spatial resolution provided by these data improve the current model of light-scattering haze formation in wounded corneas, which will improve the design of studies aimed at maintaining corneal clarity following acute injury or surgery.